Application of Decomposer Bacteria Origin From Gold Snail Combination With Goat Rumen To Manufacture Empty Palm Bunch Compost : Aplikasi Bakteri Dekomposer Asal Keong Mas Kombinasi Rumen Kambing Untuk Pembuatan Kompos Tanda Kosong Kelapa Sawit - -, Fauzan; Rusmini, Rusmini (Politeknik Pertanian Negeri Samarinda, 2024)
In East Kalimantan, there exist broad oil palm estates spreading over 1,312,095 hectares, yielding an all out creation of 3,750,607 tons. These plantations produce a lot of waste, especially empty oil palm fruit bunches (EFB), which are hard to break down because they are made of a lot of cellulose. One strategy for dealing with this waste is treating the soil, using microorganisms equipped for cellulose decay, like microscopic organisms and parasites. This study intends to assess fertilizing the soil term, examine fertilizer actual properties, and evaluate supplement content, including N, P, K, C/N proportion, and pH. Two strategies were looked at: one utilizing decaying microbes from brilliant snails joined with goat rumen (P1), and the other using a business bioactivator (P2). From June to September 2023, this study compared each method's fertilization results to Indonesian National Standard (SNI) No.19-7030-2004. According to the findings, both the P1 and P2 approaches required 53 days to compost EFB waste. Albeit the last manure temperature stayed predictable at 28ºC for the two strategies, P2 showed prevalent qualities with regards to variety, scent, and surface. Manure from P2 showed a blackish-earthy colored tone, was scentless, and had a marginally brittle surface. In addition, nutrient analysis revealed that P2 met the requirements of SNI 19-7030-2004 with parameters for N, P, and K that were superior, with N = 1.0343%, P = 0.2554%, and K = 32.58%, respectively.